ECOWAS Economic Partnership Agreement with the EU and Nigerian Trade and Development - von Uexkull, Erik Jan; Njinkeu, Dominique; Maur, Jean-Christophe; Coste, Antoine; Shui, Lulu (World Bank, Washington, DC, 2015)
This paper offers a simple way to assess the impact on the economy of Nigeria of an economic partnership agreement (EPA) between the ECOWAS countries and the European Union (EU) , based on the market access offer contained in the negotiation proposals in early 2014 with the following key elements: liberalization, to the benefit of the EU, of West African market access for 75 percent of tariff lines over a period of 20 years; three categories of products subject to gradual liberalization, in four stages of five years each, starting on December 31, 2019 for the first category being liberalized and finishing in 2035 for the third category. The fourth category of products, representing one quarter of all tariff lines, is not subject to liberalization; and possibility of recourse to trade defense measures, including bilateral safeguard measures (article 22) and an infant industry clause (article 23). The analysis presented in this paper is based on a new methodology that combines the advantages of a partial equilibrium modeling framework with the wealth of firm level information contained in a World Bank enterprise survey for Nigeria. The intention is to add value to the policy debate around the EPA by generating results that are intuitive and transparent to a non-technical audience, and that rely on a limited number of simple assumptions, while adding precision and detail to the expected impact on the domestic economy.